PENGARUH LAYANAN, PROMOSI, DAN DISKON TERHADAP KEPUTUSAN PEMBELIAN LAYANAN MELALUI APLIKASI MAXRIDE DI KOTA MEDAN - Iskandar Sopang, Fandi; Antoro2, Budi; Junaidi, Listya (Jurnal Gici Jurnal Keuangan dan Bisnis, 2025)
In the city of Medan, there are many online transportation services such as Go-Jek, Grab, Maxim, and indriver. However, in 2024, Maxride arrived in Medan as an online transportation service in the form of Bajai. Based on an interview with Jun Franco Purba, National Service Manager of PT BAJAJ AUTO INDONESIA, there are currently more than 150 Bajai units operating in Medan. In addition, this Bajaj-style transportation has its own appeal among children and also serves as a way to cure nostalgia among parents. However, the increasingly fierce business competition, especially from similar companies, requires companies to move faster in finding consumers. The purpose of this study is to determine the factors that influence the purchasing decisions of Maxride app users in the city of Medan. The research method used is quantitative research using SEM (SmartPLS) analysis. The population in this study consisted of 2,245 users, and the sample was taken using the Slovin formula with a margin of error of 10%, resulting in a sample size of 96 respondents. The results show that the variables of service and promotion have a significant effect on the purchasing decisions of Maxride app users, accounting for 88.2%. However, the discount variable does not have a significant effect on purchasing decisions. These findings indicate that the purchasing decisions of active users are more influenced by factors such as convenience, service quality, response speed, and the effectiveness of informative promotions than by price discounts. Discounts are considered to have no significant impact due to their inconsistent nature, relatively small discount values, and the fact that purchasing decisions are more driven by user needs and loyalty to the service